VULNERABILITY AND ADAPTATION TO CLIMATE CHANGE IN RAJASTHAN - Mohapatra, Geetilaxmi; George, Meera; Pandey, Suchitra (Economic Annals, 2022)
Climate change is a globally challenging phenomenon that is particularly distressing for the agricultural sector, as agricultural products and productivity depend on the climate. This study analyses agricultural households’ perception of climate change and the adaption strategies undertaken to mitigate it. A purposive random sampling technique is used to collect primary data from a survey conducted in the arid and semi-arid regions of Rajasthan, India. The study employs logistic regression to identify the determinants of the perception of climate change and adaptation strategies, while a livelihood vulnerability index is constructed to indicate households’ degree of vulnerability, focusing especially on adaptive capacity. Out of the total sample of 600 households analysed, 534 perceive a long-term change in the climate. Farmers’ adaptation strategies include crop diversification, mixed cropping, crop rotation, and farm ponds. The major factors affecting adaptation are the educational status of the household head, farming experience, type of financial support, agricultural training, land size, access to agricultural institutions, distance between the household and farmland, and storage. The livelihood vulnerability index shows that most of the households are moderately vulnerable. The study recommends an efficient weather forecasting system and effective government policies to improve credit availability, financial support, and agricultural mechanization.